2020
DOI: 10.1136/bmjopen-2020-037406
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Symptom Screening in Paediatrics Tool (SSPedi) into North American Spanish and Among Spanish-speaking children receiving cancer treatments: evaluating understandability and cultural relevance in a multiple-phase descriptive study

Abstract: ObjectivesSymptom screening is important to achieving symptom control. Symptom Screening in Paediatrics Tool (SSPedi) is validated for English-speaking children. Objectives were to translate SSPedi into Spanish, and to evaluate the understandability and cultural relevance of the translated version among Spanish-speaking children with cancer and paediatric haematopoietic stem cell transplant recipients.MethodsWe conducted a multiphase, descriptive study to translate SSPedi into Spanish. The first step was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As previously described, we convened a panel consisting of Spanish-speaking investigators and translators from the USA, Canada and Argentina. 9 The documents translated were as follows: instructions for completing SSPedi, each symptom, the degree of bother response scale and a synonym list of symptoms for patients who had difficulty understanding a symptom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, we convened a panel consisting of Spanish-speaking investigators and translators from the USA, Canada and Argentina. 9 The documents translated were as follows: instructions for completing SSPedi, each symptom, the degree of bother response scale and a synonym list of symptoms for patients who had difficulty understanding a symptom.…”
Section: Methodsmentioning
confidence: 99%
“… 8 We also focused on translation to Spanish. 9 During this translation process, we identified that at least two versions of Spanish would be required, namely, one appropriate for North America and one appropriate for Argentina. This distinction arose from differences in common language, grammatical structure and use of voseo conjugation in Argentina.…”
Section: Introductionmentioning
confidence: 99%